The Relationship Of Industrial Work Practices And Learning Motivation To Job Preparation - Wulandari, Yuka; Andriani, Cici; Elida, Elida; Zulfikar, Dikki (Universitas Negeri Padang, 2024)
This research aims to describe the relationship between industrial work practices and learning motivation on students' readiness to enter the world of work in class XII Bukittinggi. In this research, measurements will be taken to determine the relationship between industrial work practices and learning motivation on students' readiness to enter the world of work. This research is a type of correlation research using a quantitative approach. The population was students of class Based on the results of hypothesis testing, it can be seen that industrial work practices and learning motivation have a very good relationship with readiness to enter the world of work for XII Culinary students at SMKN 2 Bukittinggi. This can be seen based on the correlation figures, namely Rcount > Rtable 0.825 > 0.288. It can be seen that the relationship between the variables of industrial work practices and learning motivation and work readiness has a perfect relationship because it is between 0.810-1.000. Based on the f test, it can be seen that the Sig. for variable SMKN 02 Bukittinggi.